2018
DOI: 10.15587/1729-4061.2018.140984
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the properties of antifriction composites based on aluminum alloy's grinding waste

Abstract: Розроблено антифрикцiйнi композити на основi регенерованих шлiфувальних вiдходiв алюмiнiєвого сплаву АМ4,5Кд з додаванням твердої змащувальної речовини МоS 2 , що призначенi для роботи у контактних парах постдрукарських машин, таких як фальцювально-клейовi машини та машини для вклеювання в пакування. Аналiз структури нового композиту показав, що легуючi елементи металевої основи утворюють змiцнюючi фази, що рiвномiрно розподiленi в матрицi без сегрегацiйних скупчень, що сприяє пiдвищенню конструкцiйної мiцност… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…Для оснащення вузлів тертя швидкісних ротаційних друкарських машин авторами [4][5][6][7][8][9][10][11][12] Так, застосування ельборового шліфування кругами зернистістю 14-28 мкм на бакелітно-гумовій зв'язці забезпечило мінімальні величини параметру шорсткості R a = 0,230-0,310 мкм, що дає змогу рекомендувати такі режими обробки: для плоского ельборового шліфування -швидкість кругу -22 м/с, поздовжня подача -2 м/хв, поперечна подача -0,1 мм/подв. хід; глибина різання -2 мкм; для круглого зовнішнього ельборового шліфування -швидкість кругу 40 м/с, швидкість обертання деталі 30-40 м/хв, поздовжня подача 25-35 мм/об.…”
Section: постановка проблемиunclassified
“…Для оснащення вузлів тертя швидкісних ротаційних друкарських машин авторами [4][5][6][7][8][9][10][11][12] Так, застосування ельборового шліфування кругами зернистістю 14-28 мкм на бакелітно-гумовій зв'язці забезпечило мінімальні величини параметру шорсткості R a = 0,230-0,310 мкм, що дає змогу рекомендувати такі режими обробки: для плоского ельборового шліфування -швидкість кругу -22 м/с, поздовжня подача -2 м/хв, поперечна подача -0,1 мм/подв. хід; глибина різання -2 мкм; для круглого зовнішнього ельборового шліфування -швидкість кругу 40 м/с, швидкість обертання деталі 30-40 м/хв, поздовжня подача 25-35 мм/об.…”
Section: постановка проблемиunclassified
“…The results showed that the samples with high iron content had greater wear resistance and hardness, but the friction coefficient would be improved, demonstrating that the iron phase enhanced the wear resistance of recycled aluminum. 16,17 These studies have contributed to the application of plastic forming of recycled aluminum alloys in production. There has been a great deal of research on the production processes and intermetallic compounds, but little research has been conducted on the effects of recycled aluminum alloy defects on plastic forming.…”
Section: Introductionmentioning
confidence: 99%
“…The authors initiated research work on the regeneration and subsequent use of some types of ferrous and non-ferrous metal-based grinding waste to obtain new bearings, and promising results were obtained [5][6][7]. Such studies are one of the first steps in using grinding metal waste to make new antifriction composites.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this study represents an innovative topic in the relevant field of knowledge, which was started by the authors of [5][6][7]. The complexities arise in grinding waste regeneration problems, development of the manufacturing processes, features of the anisotropic composites structure and their properties, the behavior of materials in the process of friction at high temperatures, loads, etc.…”
Section: Introductionmentioning
confidence: 99%